MENINGKATKAN KESADARAN TENTANG KEUNTUNGAN GENRE DAN MULTIMODALITAS UNTUK TUJUAN PENERJEMAHAN: KASUS GENRE TEKS PROMOSI - Kristina, Diah (Jurnal Penerjemahan, 2014)
This article aims at showing how the perspectives of genre and multimodality contribute significantly to the pre-translation process. Ability to digest the source text and to transfer it into an equal target text therefore fulfill part of the competencies of a qualified translator. Five advertorial texts of Garuda Indonesia are scrutinized to see their micro and macro structures. By using genre perspective, components of the texts like communicative purpose, institutional and cultural agenda, ideology of the writer, how the writer positions his/her readers, the generic convention in terms of lexis, syntax, rhetorical structure and rhetorical devices are seen integratedly. Since all texts are multimodal (Kress, 2010), the advertorials of Garuda Indonesia are therefore representing ensembles of modes which are specifically selected by the sign maker. By using these approaches, this article has shown a model of looking at promotional texts for translation purposes in which a series of steps needs to be adopted.